Nephropathogenic Infectious Bronchitis Virus Infection Altered the Metabolome Profile and Immune Function of the Bursa of Fabricius in Chicken - Kuang, Jun; Xu, Puzhi; Shi, Yan; Yang, Yitian; Liu, Ping; Chen, Shupeng; Zhou, Changming; Li, Guyue; Zhuang, Yu; Hu, Ruiming; Hu, Guoliang; Guo, Xiaoquan (Frontiers in Veterinary Science, 2021)
Infectious bronchitis is a highly contagious, acute viral respiratory disease of chickens, regardless of the strain, and its infection may lead to considerable economic losses to the poultry industry. New nephropathogenic infectious bronchitis virus (NIBV) strains have increasingly emerged in recent years; hence, evaluating their infection-influenced immune function changes and the alteration of metabolite profiling are important. Initially, chickens were randomly distributed into 2 groups: the control group (Con) and the disease group (Dis). Here, the partial cytokines were examined, and the metabolome alterations of the bursa of Fabriciusa in NIBV infections chickens were profiled by GC‑TOF/MS. The results revealed that the NIBV infection promotes mRNA expression of inflammatory cytokines. Metabolic profile analysis indicated that clustering differed between the two groups and there were 75 significantly differently metabolites detected in the two groups, suggesting that the host metabolism was significantly changed by NIBV infection. Notably, the following 12 metabolites were identified as the potential biomarkers: 3-Phenyllactic acid, 2-Deoxytetronic acid, Aminomalonic acid, Malonamide 5, Uric acid, Arachidonic acid, 2-Methylglutaric Acid, Linoleic acid, Ethanolamine, Stearic acid, N-alpha-Acetyl-L-ornithine and O-acetylserine. Furthermore, the results of the correlation analysis between metabolic biomarkers and inflammatory cytokines showed that there is a strong correlation between them. Our findings describes an immune and metabolic profile for the bursa of Fabriciusa of chickens when infected with nephropathogenic infectious bronchitis virus and provides new biomarkers of NIBV infection as potential targets and indicators of indicating and therapeutic efficacy.